2013
DOI: 10.1007/s13205-013-0179-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of lignocellulosic waste to bioethanol by Trichoderma and yeast fermentation

Abstract: The present work aimed at producing bioethanol using lignocellulosic waste sawdust and marine yeast fermentation. Lignocellulosic waste materials were converted into monosugars through acid hydrolysis and finally treated with cellulase enzyme derived from Trichoderma/Hypocrea. To enhance the conversion of the glucose from sawdust, the experimental conditions were statistically optimized. The efficient conversion of sawdust to glucose of 78.56 % was achieved under the conditions of pH 6.19, temperature 29 °C, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…At present, the conversion of low-value agriculture wastes into valuable commodities, energy, chemicals and microbial protein by saccharification and fermentation processes is not economically feasible, largely due to the costs of cellulosic materials and cellulolytic enzymes, as well as technical problems associated with cellulose saccharification. 1 , 2 , 3 , 4 , 5 There is an increased interest in using thermophilic bacteria Geobacillus stearothermophilus for the production of cellulases and separate saccharification and fermentation of lignocellulosic biomass due to their higher operating temperatures and broad substrate range. 6 , 7 The complete cellulose hydrolysis can be achieved by a combination of three types of cellulases: endoglucanases, which cleave internal glucosidic bonds; exoglucanases, which cleave cellobiosyl units from the ends of cellulose; and glucosidase, which cleaves glucose units from cello-oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the conversion of low-value agriculture wastes into valuable commodities, energy, chemicals and microbial protein by saccharification and fermentation processes is not economically feasible, largely due to the costs of cellulosic materials and cellulolytic enzymes, as well as technical problems associated with cellulose saccharification. 1 , 2 , 3 , 4 , 5 There is an increased interest in using thermophilic bacteria Geobacillus stearothermophilus for the production of cellulases and separate saccharification and fermentation of lignocellulosic biomass due to their higher operating temperatures and broad substrate range. 6 , 7 The complete cellulose hydrolysis can be achieved by a combination of three types of cellulases: endoglucanases, which cleave internal glucosidic bonds; exoglucanases, which cleave cellobiosyl units from the ends of cellulose; and glucosidase, which cleaves glucose units from cello-oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows the comparison of bioethanol production by different strains of S. cerevisiae from various types of lignocellulosic biomass via SSF at higher temperatures. Saravanikumar and Kathiresan [ 50 ], in their studies on sawdust, reported that sawdust hydrolysate was produced by consecutive acid treatment and enzymatic hydrolysis, using cellulase from Trichoderma estonicum SKS1. Bioethanol was produced via SHF by S. cerevisiae JN387604 at 36.5 °C, obtaining an ethanol concentration of 55.2 g/L and a theoretical yield of 85.6% at a fermentation period of 102 h. Recently, waste jasmine flower has been used as substrate for bioethanol production.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, basidiomycetes, for example, Phanerochaete chrysosporium, have been found to degrade farm waste [81,127]. The pretreatment of agricultural pulp waste employed Streptomyces and white-rot fungi for the degradation of lignin where lignin reduction was measured in hard wood (23.5%) and soft wood (10.5%) [128]. Delignification (85.6%) was attained in sawdust by a 55.2 g/L pretreatment with a cellulose enzyme (derivative of Trichoderma/Hypocrea) [128].…”
Section: Biological Pretreatment Of Wastewatermentioning
confidence: 99%